Seroprevalence and prevalence of Babesia vogeli in clinically healthy dogs and their ticks in Costa Rica - Dolz, Gaby (2021)
Canine babesiosis is a disease caused by a parasite of the genus Babesia which destroys red blood cells. Previous studies have shown the presence of Babesia vogeli in rural areas in Costa Rica using molecular techniques. The objective of the present study was to determine the seroprevalence and prevalence of B. vogeli in clinically healthy dogs and their ticks at the national level, both within and outside the Central Valley. Blood samples and ticks from 482 dogs were collected between June 2011 and May 2014, and analyzed by immunofuorescence assay (IFA) and real-time polymerase chain reaction (qPCR); two protocols of endpoint PCR and sequencing were used to confrm qPCR-positive samples. Seroprevalence of canine babesiosis of 5.3% (24/453) was determined at the national level, specifcally 2.0% (5/253) within and 9.5% (19/200) outside the Central Valley, respectively. Real-time PCR determined a global prevalence of B. vogeli of 31.3% (125/400): 21.4% (47/220) within the Central Valley and 43.3% (78/180) outside the Central Valley. The endpoint PCR amplifed only 10 of the 125 blood samples identifed as positive in qPCR. One sample amplifed by endpoint PCR was sequenced and identifed as B. vogeli. Twelve canines were identifed with past infections, seven canines with active infection, and 111 canines with early infection. Two species of ticks were found with B. vogeli: Rhipicephalus sanguineus sensu lato (n=40) and Amblyomma ovale (n=1). The prevalence of canine babesiosis at the national level, both within and outside the Central Valley, is reported here for the frst time, determining the presence of the piroplasmid throughout the country, with a higher circulation of the agent outside the Central Valley. Only one species, B. vogeli, was detected in the blood of dogs and their ticks. Therefore, veterinarians should consider using qPCR to determine the presence of the parasite in blood donors and before starting treatment of vector-borne disease in dogs.